Spindle-like MIL101(Fe) decorated with Bi2O3 nanoparticles for enhanced degradation of chlortetracycline under visible-light irradiation - Hao, Chen-chen; Chen, Fang-yan; Bian, Kun; Tang, Yu-bin; Shi, Wei-long (Beilstein Journal of Nanotechnology, 2022)
Improving the photocatalytic performance of metal–organic frameworks (MOFs) is an important way to expand its potential applications. In this work, zero-dimensional (0D) Bi2O3 nanoparticles were anchored to the surface of tridimensional (3D) MIL101(Fe) by a facile solvothermal method to obtain a novel 0D/3D heterojunction Bi2O3/MIL101(Fe) (BOM). The morphology and optical properties of the as-prepared Bi2O3/MIL101(Fe) composite were characterized. The photocatalytic activity of the synthesized samples was evaluated by degrading chlortetracycline (CTC) under visible-light irradiation. The obtained BOM-20 composite (20 wt % Bi2O3/MIL101(Fe)) exhibits the highest photocatalytic activity with CTC degradation efficiency of 88.2% within 120 min. The degradation rate constant of BOM-20 toward CTC is 0.01348 min−1, which is 5.9 and 4.3 times higher than that of pristine Bi2O3 and MIL101(Fe), respectively. The enhanced photocatalytic activity is attributed to the formation of a Z-scheme heterojunction between Bi2O3 and MIL101(Fe), which is conducive to the rapid separation of photogenerated carriers and the enhancement of photogenerated electron and hole redox capacity. The intermediate products were analyzed by liquid chromatography–mass spectrometry (LC–MS), and a possible photocatalytic degradation path of CTC was proposed. This work provides a new perspective for the preparation of efficient MOF-based photocatalysts.
Keywords: Bi2O3; chlortetracycline; metal–organic frameworks; MIL101(Fe); photocatalysts; Z-scheme heterojunction